Verification of getting on and off a simulated diesel vehicle using a wheelchair equipped with a 4-degree-of-freedom arm mechanism - Fumiaki TAKEMORI (Nihon Kikai Gakkai ronbunshu)
In recent years, railway operators have been promoting the construction of unmanned stations, and the ratio of unmanned stations is increasing year by year. However, unmanned stations have a disadvantage for passengers who need assistance when boarding and disembarking, in that they cannot receive on-demand assistance. It has been reported that the rate of unmanned stations is higher on regional lines than in urban areas. Since many local routes are not electrified, most of the trains operated are diesel railcars. Diesel railcars are vehicles powered by diesel engines, and because the engine is mounted under the bogie floor, access to the vehicle floor is via a step structure that is raised one step from the vehicle entrance. For wheelchair users, the accessibility to the multi-level entrances/exits of diesel railcars via existing grooves in station platforms is significantly reduced. In this paper, we propose a mechanism and its control system to assist wheelchair users in getting on and off public transportation vehicles. This mechanism has a mobility function that combines lifting and lowering with a ground arm and a running function with wheels, and consists of an arm mechanism with two degrees of freedom and a running mechanism that can be added to the front and rear of an existing wheelchair. This paper demonstrates the feasibility of using this mechanism to enable a wheelchair user to board and disembark from a diesel railcar, and also discusses step-crossing motion that quantitatively suppresses the jerking motion that occurs when going up and down steps.